Evaluation of early outcomes of surgical fixation in metacarpal and phalangeal fractures - Dang, Le Hoang Nam; Nguyen, Ba Luu; Le, Nghi Thanh Nhan (Tạp chí Y Dược Huế, 2026)
Background: Metacarpal and phalangeal fractures are common injuries of the upper extremity. Surgical treatment allows accurate reduction, stable fixation, and early functional rehabilitation. Various fixation techniques have been applied, including Kirschner wire (K-wire) fixation, intramedullary fixation, external fixation, mini-plate and screw fixation, or combinations thereof. Objective: Evaluation of early surgical outcomes in metacarpal and phalangeal fractures treat with mini-plates/screws or Kirschner wires. Materials and Methods: This prospective descriptive study included 33 patients with metacarpal and/or phalangeal fractures indicated for surgical fixation using mini-plates and screws or Kirschner wires at the Department of Orthopedic Trauma and Thoracic Surgery, Hue University of Medicine and Pharmacy Hospital. Clinical, radiographic characteristics and treatment outcomes were assessed at 3 months postoperatively using the ASSH scoring system. Results: The mean age was 39.16 years; the male-to-female ratio was 2.67:1. At 3 months, radiographic bone union was achieved in 94.7% of cases, while delayed union occurred in 5.3%. According to ASSH criteria, range-of-motion outcomes were excellent in 63.2%, good in 34.2%, and fair in 2.6% of cases. The mean total active motion (TAM) at 3 months postoperatively was 231.27 ± 9.96°. Conclusion: With a low complication rate and favorable early functional recovery, surgical fixation is an effective treatment for metacarpal and phalangeal fractures, helping to avoid joint stiffness commonly associated with prolonged cast immobilization.